Assessing self-forgiveness through the Enright Self-Forgiveness Inventory in the Spanish population: a validation study - Molinero, Clara; Kasprzak, Agata; Bonete, Saray; Gallo-Giunzioni, Karla (Frontiers in Psychology, 2023)
Introduction: Self-forgiveness has been a complex construct to define, which has resulted in a shortage of instruments that adequately measure it as a process. In Spain, until now there is only one validated instrument to measure self-forgiveness, for this reason the present study aims to validate the Enright Self-Forgiveness Inventory (ESFI).Method: A sample of 276 people (84 men, 192 women) aged from 18 to 25 years, completed the Enright Self-Forgiveness Inventory (ESFI) after its adaptation to Spanish, as well as the Enright Forgiveness Inventory-30 (EFI-30), the Narcissistic Personality Inventory (NPI), the Short form of Social Desirability Scale (M-C SDS), the Scale of psychological wellbeing (RYFF) and the Depression, Anxiety and Stress Scale-21 (DASS-21) Results: The Confirmatory Factor Analysis showed a good fit for the original six-factors structure (CFI=.93, TLI=.92, RMSEA= .063). The results showed good psychometric qualities (both validity and reliability) and association between self-forgiveness and social desirability, depression, anxiety, narcissistic traits, and purpose in life as expected theoretically.Discussion: The ESFI-30 shows good psychometric properties within the Spanish context and is an appropriate instrument for evaluating self-forgiveness for research and clinical intervention. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership. References should not be cited in the abstract. Leave the Abstract empty if your article does not require oneplease see the "Article types" on every Frontiers journal page for full details.